Antimicrobial Activity of the Plant Syzygium alternifolium - APPALA RAJU, V.V.S.S.; RAMESH, M.; LAKSHMI NARSAU, M.; MURALIKRISHNA KUMAR, M. (Asian Journal of Chemistry, 2010)
Extracts of leaves of the plant Sygygium alternifolium were tested for antibacterial and antifungal activity. This study revealed good antifungal activity for the non-polar extracts and good antibacterial activity was observed in ethyl acetate and alcoholic extracts.